Exploring the law of color presentation of double-sided heterochromatic digital printing for textile - Duan, Yiting; Zhang, Min; Zhou, Jiu; Zhou, Hua; Xu, Liming; Yang, Heng (Frontiers in Psychology, 2022)
With the upgrading of production technology and design aesthetic of textile products, the development and application of double-sided digital printing technology has been gradually proposed in recent years. The production of double-sided heterochromatic digital printing requires high accuracy for color management as in the production process, different input devices, display devices and output devices each have varying color processing capabilities and color performance characteristics, which leads to the transfer of color between different devices can not accurately reproduced. However, there is little research involved in the color formation laws in the design and production of double-sided heterochromatic digital printing. The purpose of this paper is to explore the prediction model of color presentation in double-sided heterochromatic digital printing. Due to the influence of the fabric thickness, the gap between the textile structure and the infiltration rate of the printing pigments, the color of each side in double-sided, heterochromatic printing results often differs from the designed color. In this paper, taking chiffon fabric, which is one of the thinnest and has strongest permeability in silk fabric, as an example fabric base; select 24 colors from 6 hue angles and 4 chromas as experimental colors. According to the color gamut of the digital printing machine, 15 out of 24 colors were selected as experimental colors. These 15 colors were printed on two sides in pairs to generate 225 color pairs as double-sided experimental samples. For these experimental samples, this paper conducts experiments from both subjective and objective aspects through the combination of subjective evaluation of psychophysics experiments and objective instrument measurement. Through the analysis of experimental data, the color difference prediction under subjective models (R²=0.57) and objective model(R²=0.73) are given respectively. The dominant color prediction model (R²=0.77) during double-sided heterochromatic digital printing was also been built. The combination of the three models can predict the color regularity of double-sided heterochromatic digital printing on silk, which may have certain significance for the design and development of silk double-sided heterochromatic digital printing products.